Pesticide application and equipment technology used in the local agricultural industry - Sharmila, Binti Zainal Abidin. (unimas, 2004)
Pesticide can be classified into three categories, namely herbicide, insecticide and fungicide. Based on the study made in three major Malaysia's plantations, namely oil palm, cocoa and pepper plantation, it was found that oil palm plantation focuses on high capital cost mechanization in applying pesticide. However, in cocoa and pepper plantation, manually carried equipment such as lever-operated knapsack sprayer is commonly used. Spray characteristics for the three types of hydraulic nozzle, namely 48A brass, plastic cone and LSA-4 nozzle, which are commonly found in local plantations were discussed in this report. A novel electrostatic sprayer for application to the local plantation was also discussed